Efeitos da temperatura nas respostas cardio-respiratórias e na respiração aérea acessória de JEJU, Hoplerythrinus unitaeniatus (Erytrinidae) aclimatados a 15, 20, 25 e 30°C e submetidos a variações de O2 ambiental - Oliveira, Rosenil Dias de (Universidade Federal de São Carlos, 2003)
Tropical fish generally inhabit environments with high temperatures and low dissolved oxygen. Along the evolutionary process several species developed mechanisms of air-breathing in order to compensate the oxygen demands caused by the aquatic hypoxia. These mechanisms required anatomical, physiological and biochemical adaptations. Studies on the effects of hypoxia and temperature changes on fish involve the comprehension of the cardio-respiratory mechanisms of compensation. The present study was addressed to determine the cardio-respiratory and air-breathing responses of jeju, Hoplerythrinus unitaeniatus, which utilize the swimming bladder as an organ for accessory respiration in the air, submitted to gradual hypoxia after acclimation to 15, 20, 25 and 30oC. The oxygen uptake ( &VO2 ), gill ventilation ( G V& ) breathing frequency (fR), ventilation volume (VT) and the O2 extraction from the ventilatory current (EO2) were obtained for specimens of jeju (Wt = 209,7 ± 5 g) by flow-trough respirometry. The air-breathing frequency (fRA) and time spent in air-breathing (TRA) were determined by means of an experimental chamber specially constructed for this purpose. Independently of the acclimation temperature, jeju responded to hypoxia as an oxyregulator, i. e., the species was able to keep constant &VO2 in response to graded hypoxia until reach a critical oxygen tension (PcO2). The mean &VO2 values at each acclimation temperature, before reaching the PcO2, were: 47 ± 0,8 mlO2.kg-1h-1 (15°C), 82 ± 0,3 mlO2.kg-1h-1 (20°C), 104 ± 2,6 mlO2.kg-1h-1 (25°C) and 112 mlO2.kg-1h-1 (30°C). The PcO2 for each acclimation temperature were 28, 33, 41 e 52 mmHg, respectively. The increased reductions on PcO2 as acclimation temperatures rose from 15 to 30oC showed that this species presents partial compensation (or type 3 compensation) to temperature increases. Jeju increased the G V& to compensate the graded hypoxia due to higher increments on VT than in fR. This kind of compensation, however, was not enough to keep a constant EO2, which decreased gradually in response to graded hypoxia in all acclimation temperature. At 25 and 30°C the fH were significantly higher than at 15 and 20oC. Hypoxic bradicardia was not recorded at 15 and 20oC and at 25 and 30°C it only occurred below the PcO2. The different PcO2 were also the threshold for the development of accessory air-breathing in all acclimation temperatures. Increases in both fRA and TRA were inversely proportional to the water PO2 reductions and directly proportional to the acclimation temperature.
Keywords: Teleósteos; Função cardio-respiratória; Temperatura; Respiração aérea; Aclimatação; Consumo de O2; Ventilação branquial; Freqüência respiratória; Volume ventilatório; Extração de O2; Função cardiorespiratória; Respiração aérea; Hoplerythrinus unitaeniatus; Temperature; Acclimation; Oxygen uptake; Gill ventilation; Breathing frequency; Ventilation volume; O2 extraction; Function cardio-respiratory; Airbreathing; Hoplerythrinus unitaeniatus; CIENCIAS BIOLOGICAS::ECOLOGIA